Ecophysiological responses of seedlings of six dipterocarp species to short-term drought in Borneo - Ichie, Tomoaki; Igarashi, Shuichi; Tanimoto, Tomoko; Inoue, Yuta; Mohizah, Mohamad; Kenzo, Tanaka (Frontiers in Forests and Global Change, 2023)
To predict the dynamics of tropical rainforest ecosystems in response to climate change, it is necessary to understand the drought tolerance and related mechanisms of trees in tropical rainforests. In this study, we assessed the ecophysiological responses of seedlings of six dipterocarp species (Dipterocarpus pachyphyllus, Dryobalanops aromatica, Shorea beccariana, S. curtisii, S. parvifolia, and S. smithiana) to experimental short-term drought conditions. The seedlings were initially grown in plastic pots with sufficient irrigation; irrigation was then stopped to induce drought. Throughout the soil-drying period, we measured various ecophysiological parameters, such as maximum photosynthetic and transpiration rates, stomatal conductance, water-use efficiency, predawn water potential, the maximum quantum yield of photosystem II (Fv/Fm), leaf water characteristics (using pressure-volume curves), leaf water content, and total sugar and starch contents. In all six dipterocarp species studied, the Fv/Fm values dropped sharply when the soil water content fell below 8%. However, there were interspecific differences in physiological responses to such a decrease in soil water content: S. parvifolia and S. beccariana actively controlled their stomata during drought to reduce water consumption via an isohydric response, but showed an increase (S. parvifolia) or no change (S. beccariana) in leaf drought tolerance; Di. pachyphyllus and Dry. aromatica maintained photosynthesis and transpiration close to the wilting point during drought without reducing water consumption via an anisohydric response, and also increased their leaf drought tolerance over the drying period; and S. curtisii and S. smithiana maintained their photosynthetic capacity without stomatal closure, but showed no change or a slight decrease in leaf drought tolerance. Our results indicate that extreme drought can cause the death of dipterocarp seedlings via various drought response, which could substantially impact the future distribution, population dynamics, and structure of tropical rainforests.